2006
DOI: 10.1111/j.1600-6143.2006.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone Exposure in Pediatric Renal Transplant Patients

Abstract: Glucocorticoid (GC) dosing is commonly based on body mass or surface area in children, although the drug effects appear to correlate with steroid exposure, rather than dose. We compared the area under the serum concentration-time curve (AUC) of methylprednisolone (MP) with a recombinant cell bioassay measuring serum glucocorticoid bioactivity (GBA), in prediction of side effects in 16 pediatric patients (5.4-18.4 years of age) 2.0-14.9 years after renal transplantation (TX). They received 0.3 mg/kg of MP orall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…1 In infants, the kidney graft can be placed intraperitoneally (a) or extraperitoneally (b) [44]. The other possibility is to switch to low-dose (0.1 mg/kg/ day), every-other-day medication, which also effectively abolishes the steroid side effects [45,46].…”
Section: Peri-and Postoperative Managementmentioning
confidence: 99%
“…1 In infants, the kidney graft can be placed intraperitoneally (a) or extraperitoneally (b) [44]. The other possibility is to switch to low-dose (0.1 mg/kg/ day), every-other-day medication, which also effectively abolishes the steroid side effects [45,46].…”
Section: Peri-and Postoperative Managementmentioning
confidence: 99%
“…Steroid therapy inhibits growth by both interfering with the hypothalamus-pituitary/growth hormone/insulin-like growth factor axis and having a direct effect on bone formation (see below). Pharmacokinetic studies of methylprednisolone in pediatric liver and kidney transplant recipients have demonstrated that the area under the serum concentration–time curve (AUC) rather than dose was predictive for growth retardation [30, 31]. However, this correlation between AUC and growth was not unanimously found in transplanted children treated with prednisone or prednisolone [32].…”
Section: Factors Influencing Growth Post-transplantationmentioning
confidence: 99%
“…(40) Because GC exposure varies individually and control of adverse effects is important, measurement of serum GC bioactivity may give an additional tool for monitoring GC exposure. (41) Also, variable results have been obtained with different GC preparations used in children. (42) Overall, the effects of GC on a growing skeleton are still quite unclear.…”
mentioning
confidence: 99%